Deskripsi Model Mental Peserta Didik pada Materi Termokimia Kelas XI SMAN 2 Padang - Farah Nalsha Laila Putri; Dwi Finna Syolendra (MASALIQ, 2026)
The low achievement in the 2025 Senior High School Chemistry Academic Competency Test (TKA) indicates that students’ understanding of chemistry concepts remains suboptimal, particularly in abstract topics such as thermochemistry, which may lead to the formation of mental models that are inconsistent with scientific concepts. This study aimed to describe students’ mental models in thermochemistry as a basis for evaluation in improving the quality of Grade XI chemistry learning at SMAN 2 Padang. This study used a qualitative approach with a descriptive design, involving 30 students selected through random sampling. Data were collected using an essay test instrument that had been validated by experts with an Aiken’s V coefficient of 0.903, and were then analyzed descriptively and qualitatively based on the alignment of students’ answers with scientific concepts. The results showed that students’ mental models were still dominated by the Initial Model and Synthesis Model categories, while the Scientific Model category remained relatively low. Students still experienced misconceptions, particularly in distinguishing between system and surroundings, understanding the direction of heat transfer, and connecting macroscopic, submicroscopic, and symbolic representations. These findings indicate that students’ understanding remains at an initial stage to a transitional stage toward scientific understanding. Thus, this study contributes to mapping the profile of students’ mental models in thermochemistry and serves as a basis for developing more effective chemistry learning strategies through a multiple-representation approach and the use of visual media to help students develop mental models toward the Scientific Model category.